Media education in the school system - Walat, Wojciech (Array, 2020)
The diagnosis of the problem of the contemporary world in the area of global media communication is a basic challenge for existing and modernized educational systems. Without a complete vision of the world, people cannot exist in a fully aware way. Hence, the most important questions related to such social development in which no one would be excluded from the world-wide circulation of information. The general assumptions of common media education have been presented in the article.